Adversity quotient dengan Kecenderungan Depresi pada Driver Ojek Online di tengah Pandemi Covid-19 (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2020)
This studynaimsntondetermine the relationship of adversitynquotient with the tendency of depression in online motorcycle taxi drivers amid the covid-19 pandemic. The analysis of this study uses independent variables namely adversity quotient and the dependent variable tendency of depression. The subjects used in this study were online motorcycle taxi drivers who are members of the Surabaya online motorcycle solidarity community that has 60 active members. The research subjects were all participants involved in 60 online motorcycle taxi drivers, for the research scale researchers sent a questionnaire to the online motorcycle taxi driver. The technique of taking data is by collecting google form links which are then filled in by research subjects. The statistical method used is the Spearman Brown statistical test. The results of this study indicate that there is a negative correlation between the adversity quotient and the tendency for depression in online motorcycle taxi drivers amid the covid-19 pandemic. The existence of a negative relationship indicates thatnthe highernthe adversitynquotient, the lower the tendency for depression, and vice versa, the lowernthe adversitynquotient, the higher the tendency for depression.Keywords: Adversity quotient, Depression Tendency, Online Ojek Driver, Pandemic.